There's Always Room for One More - McGrath, Robyn; Lobo, Ishaa (New York : Simon & Schuster Books for Young Readers, 2023)
Clare struggles to say goodbye to the family table, until she discovers that a new, bigger table means more room for creating memories and welcoming loved ones.
Keywords: Family life -- Fiction; Tables -- Fiction; Families -- Juvenile fiction; Tables -- Juvenile fiction; Picture books